[Indian Pundit, Trinidad] - (:unkn) unknown (My University, 2008)
Photo of an East Indian holy man in traditional wear. No. 320910
Colour: Yellow and Red Hues; Style: Portrait; Other: Unbordered, Divided
Keywords: Postcards; Hindu priests--Trinidad and Tobago; East Indians--Trinidad and Tobago; Men--Trinidad and Tobago; Ethnic costume--India; Turbans--India; Headgear--India